Ionoskins: Ionoskins: Nonvolatile, Highly Transparent, Ultrastretchable Ionic Sensory Platforms for Wearable Electronics (Adv. Funct. Mater. 4/2020). (24th January 2020) - Kim, Yong Min; Moon, Hong Chul
Abstract : In article number 1907290, Hong Chul Moon and Yong Min Kim describe non‐volatile, highly transparent, and ultra‐stretchable ionic sensory platforms for wearable electronics. Highly deformable gels are immediately obtained by simply judiciously blending designed PMMA‐r‐PBA and [EMI][TFSI]. The resulting PMMA‐r‐PBA‐based gels are utilized in patch‐type strain sensors, referred to as ionoskins, indicating very simple device configuration, wide strain detection range, excellent stretching/releasing stability, non‐volatility without encapsulation, and high optical transparency.